Investigating the Use of Luminous Capsule Bubble Tiles in Smart Structures to Improve Reflexology - Mukilan Poyyamozhi; Panruti Thangaraj Ravichandran; Kavishri Bharathidass; Balasubramanian Murugesan; Kanniappan Vadivelan; Majed Alsafyani; Waleed Nureldeen; Narayanamoorthi Rajamanickam (Buildings)
The smart capsule bubble tile (SCBT) is an innovative flooring solution that combines acupressure-based reflexology with electromagnetic wave stimulation to enhance well-being. Designed for smart buildings and healthcare applications, SCBT integrates traditional construction techniques with advanced healing technologies to create a health-conscious, eco-friendly flooring system. For durability and thermal performance, SCBT tiles are manufactured using conventional concrete methods, enhanced with aluminum oxide (Al₂O₃). Each tile contains multiple pressure point capsules featuring a copper cap that emits electromagnetic waves when exposed to sunlight. This dual-function mechanism stimulates acupressure points on the feet, promoting better blood circulation, reducing stress, and enhancing relaxation. The heat release from the copper caps further improves thermal comfort and energy flow in the body, reinforcing the benefits of reflexology. The performance of SCBT tiles was extensively tested, demonstrating impressive physical and functional properties. They exhibit a flexural strength of 4.6 N/mm2, a thermal emissivity of 0.878, a solar reflectance of 0.842, and a water absorption rate of 8.12%. In biomechanical assessments, SCBT showed significant benefits for balance and posture correction. Users experienced a 70.8% reduction in lateral stance ellipse area with eyes open and a 50.5% reduction with eyes closed, indicating improved stability and proprioception. By integrating acupressure and electromagnetic stimulation into flooring design, SCBT promotes a holistic approach to health. This technology supports energy efficiency in smart buildings and contributes to preventive healthcare by enhancing musculoskeletal health and reducing fatigue. SCBT represents a significant step in creating built environments supporting human well-being, merging traditional healing principles with modern material science.